Public Perception of Gas Waste Pollution from the Gresik Industrial Area Based on Social Level in Sidomoro Village, Gresik District, Gresik Regency - Sekar Dewi Maharani; Muzayanah M (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Gresik Industrial Estate is an industrial area located close to residential settlements in Sidomoro Village, Gresik District, Gresik Regency, exposing the community to potential direct impacts of industrial activities. Continuous factory operations trigger high levels of air pollution. This study aims to determine public perception of gas waste pollution from the Gresik Industrial Estate and to understand community adaptation strategies to mitigate these impacts in Sidomoro Village, Gresik District, Gresik Regency. This study employs a descriptive quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to the community living around the Gresik Industrial Estate. The results indicate that the community has a high level of perception, meaning that residents strongly experience the impacts of air pollution from the Gresik Industrial Estate on their daily lives. This is evident from the high public perception of air pollution impacts at 76.89%, perceived losses due to air pollution, and disruptions to community social activities caused by air pollution at 73.78%.